(untitled) (Raparin Journal of Humanities (RJH), 2023)
Gender as a subject for study in the academic sphere gave importance and characteristics to the department that will be studied in. The main purpose of this research is to determine the importance of gender studies in media departments, in the public and private universities and colleges in the Kurdistan Region. Therefore, the main purpose of this research is to present the importance of gender studies as an independent subject in media departments. The researcher has attempted to discuss the importance of gender subject as an independent material in media departments in public and private colleges and universities in the Kurdistan Region, using a scientific quantitative and qualitative methods. The researcher has reached several conclusions: among all media departments (12 departments) in public and private universities and colleges in the Kurdistan Region, only one department is teaching gender as an independent subject. The issue of gender is unfamiliar, unfamiliar and not seriously considered. Gender is not considered as a necessary subject for some faculty members in these departments. However, proper understanding of the concept of gender in the academic setting itself is also complex and requires a scientific and objective understanding by academics and faculties. University teachers’ understanding of the importance of gender and its philosophy along with their views on this issue, is of inevitable importance and needs to be considered.